Identification of Important Sea Turtle Areas (ITAs) for hawksbill turtles in the Arabian Region - Pilcher, Nicolas J. (2014)
We present the first data on hawksbill turtle post-nesting migrations and behaviour in the Arabian region. Tracks from 90 post-nesting turtles (65 in the Gulf and 25 from Oman) revealed that hawksbills in the Arabian region may nest up to 6 times in a season with an average of 3 nests per turtle. Turtles from Qatar, Iran and the UAE generally migrated south and southwest to waters shared by the UAE and Qatar. A smaller number of turtles migrated northward towards Bahrain, Saudi Arabia and one reached Kuwait. Omani turtles migrated south towards Masirah island and to Quwayrah, staying close to the mainland and over the continental shelf. The widespread dispersal of hawksbill foraging grounds across the SW Gulf may limit habitat protection options available to managers, and we suggest these be linked to preservation of shallow water habitats and fishery management. In contrast, the two main foraging areas in Oman were small and could be candidates for protected area consideration. Critical migration bottlenecks were identified at the easternmost point of the Arabian Peninsula as turtles from Daymaniyat Islands migrate southward, and between Qatar and Bahrain. Overall, Gulf turtles spent 68% of the time in foraging ground with home ranges of 40–60km2 and small core areas of 6km2. Adult female turtles from Oman were significantly larger than Gulf turtles by ~11cm x¯=81.4CCL and spent 83% of their time foraging in smaller home ranges with even smaller core areas (~3km2), likely due to better habitat quality and food availability. Gulf turtles were among the smallest in the world x¯=70.3CCL and spent an average of 20% of time undertaking summer migration loops, a thermoregulatory response to avoid elevated sea surface temperatures, as the Gulf regularly experiences sustained sea surface temperatures >30°C. Fishery bycatch was determined for two of the 90 turtles. These spatio-temporal findings on habitat use will enable risk assessments for turtles in the face of multiple threats including oil and gas industries, urban and industrial development, fishery pressure, and shipping. They also improve our overall understanding of hawksbill habitat use and behaviour in the Arabian region, and will support sea turtle conservation-related policy decision-making at national and regional levels.